A case study on the UP International Center basement residential facility - Patindol, Abelle Joseph Don B.
With the objective of evaluating the current living conditions of the UP International Center (IC) basement as a student housing facility, this case study assessed the physical conditions, furniture layout, and the provision of amenities in the bedrooms and toilet and bath facilities of the area in question. The insights and perceptions of the dormers in terms of privacy, comfort and living experience in the IC basement were also obtained. Using convenience sampling, the study involved twelve out of fifteen male residents, four out of seven rooms, and one of the toilet and bath facilities of the IC basement. Data gathering involved observations, sketches and photo-documentation. A survey was also conducted to collect the perceptions of the residents. The data was analyzed through photo-criticism, comparison with the Building Code and planning standards, visual analysis of privacy and circulation using the theory of proxemics, and a survey evaluation. Findings of the study showed that the facility did not meet the planning standards for dorm rooms in terms of room size and furniture dimensions. Poor conditions of the toilet and bath and the lack of several amenities were also observed. Survey results showed that 92% of the respondents were satisfied with their stay in IC and 87% found the facility much better compared to other dormitories. This brought about the conclusion that, even though the IC basement did not meet the design standards of a student housing facility, it provided a satisfactory living environment for the student respondents of this study. The study recommends the renovation of the toilet and bath facilities and the application of the provision of standard furniture sizes and other necessities for the dorm bedroom. A suggested layout, based on the standards and user's needs, is presented for the dormitory bedroom as well as toilet and bath facility.